Women, gender, and technology - Fox, Mary Frank; Johnson, Deborah G., 1945-; Rosser, Sue Vilhauer (University of Illinois Press, 2006)
Looking into the co-creation of gender and technology, this work explores how gender and technology work in particular domains, including film narratives, reproductive technologies, information technology and the profession of engineering.
Keywords: Women -- Effect of technological innovations on -- United States.; Computers and women -- United States.; Information technology -- Social aspects -- United States.; Femmes, Effets des innovations sur les -- États-Unis.; Ordinateurs et femmes -- États-Unis.; Technologie de l'information -- Aspect social -- États-Unis.; Femmes -- Effets des innovations sur -- États-Unis.; SOCIAL SCIENCE / General; Computers and women; Information technology -- Social aspects; Women -- Effect of technological innovations on; United States; Frau; Technologie; USA; Vrouwen.; Technologie.; Informatietechnologie.; Sekseverschillen.; Verenigde Staten.; Aufsatzsammlung.